2021
DOI: 10.17816/ptors61685
|View full text |Cite
|
Sign up to set email alerts
|

Validation and cultural adaptation of the Russian version of the Pedi-IKDC questionnaire

Abstract: BACKGROUND: Questionnaires are standard tools used for examination of patients. Obtained data provide information about knee function disturbance and level of the quality of life. Young patients with various knee injuries also needed examination questionnaires. In worldwide practice, the Pediatric International Knee Documentation Committee (Pedi-IKDC) is more often used by doctors. However, if the doctor wants to use foreign questionnaire in his/her practice, the questionnaire should be validated and culturall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The Moroccan version of Pedi-IKDC demonstrated a good correlation between the different items in the form (Cronbach alpha= 0.7). Other validation studies [ 14 , 16 , 18 , 20 , 21 ] also showed good internal validity.…”
Section: Discussionmentioning
confidence: 81%
“…The Moroccan version of Pedi-IKDC demonstrated a good correlation between the different items in the form (Cronbach alpha= 0.7). Other validation studies [ 14 , 16 , 18 , 20 , 21 ] also showed good internal validity.…”
Section: Discussionmentioning
confidence: 81%
“…It ranges from 0 to 100, with higher scores indicating less pain and better function. Currently, it has been translated in English [17], Danish [15], Dutch [42], Italian [24], and Russian [13]. The validation studies were conducted in pediatric populations affected by a broad spectrum of knee pathologies.…”
Section: Methodsmentioning
confidence: 99%
“…They are patient‐reported questionnaires administered to patients and allow the evaluation of specific pathologies or body regions [11]. It is recommended that specifically designed PROMs should be used in children and adolescent populations [7, 14], and the pediatric version of the International Knee Documentation Committee Questionnaire (Pedi‐IKDC) is currently one of the most widely validated and reliable scores [13, 15, 17, 24, 42]. There are two main approaches for administering PROMs [1, 18].…”
Section: Introductionmentioning
confidence: 99%